Implementation of the Futsal Sports Program as a Media for Leadership Development in Elementary School Age Children - Hidayat, Hidayat; Ma’mun, Amung; Fitri, Mustika; Mahendra, Agus (Mimbar Sekolah Dasar, 2024)
Leadership is one of the important skills that need to be developed from an early age to equip children with the ability to adapt in a dynamic environment. Futsal as a team sport provides an ideal environment for developing social and leadership skills, such as cooperation, respect for differences. This study aims to explore the effectiveness of the implementation of futsal sports programs that integrate leadership development in elementary school children. The method used was an experiment with a pre-test – post-test control group design, the population of grade 6 students in SD Lembang 1, 2, and 3 with a total of 60 students, the sample used was 30 students taken from each school as many as 10 students. This study involved three groups of 6th grade elementary school children who participated in a leadership-based futsal program, a control group that participated in a futsal program without leadership integration, and a control group that did not participate in futsal and did not have leadership. Data was collected through questionnaires that measured leadership skills. The results of the study showed that the group participating in the leadership integration futsal program experienced a significant increase, with an average of 73.8. In conclusion, futsal programs that integrate leadership are effective in improving children's leadership skills and can be used as a model for character development and social skills in elementary schools.